Radiofrequency pulse design in parallel transmission under strict temperature constraints. Issue 3 (17th October 2013) - Boulant, Nicolas; Massire, Aurélien; Amadon, Alexis; Vignaud, Alexandre
<x xml:space="preserve">Abstract</x> Purpose To gain radiofrequency (RF) pulse performance by directly addressing the temperature constraints, as opposed to the specific absorption rate (SAR) constraints, in parallel transmission at ultra‐high field. Methods The magnitude least‐squares RF pulse design problem under hard SAR constraints was solved repeatedly by using the virtual observation points and an active‐set algorithm. The SAR constraints were updated at each iteration based on the result of a thermal simulation. The numerical study was performed for an SAR‐demanding and simplified time of flight sequence using B1 and ΔB0 maps obtained in vivo on a human brain at 7T. Results The proposed adjustment of the SAR constraints combined with an active‐set algorithm provided higher flexibility in RF pulse design within a reasonable time. The modifications of those constraints acted directly upon the thermal response as desired. Conclusion Although further confidence in the thermal models is needed, this study shows that RF pulse design under strict temperature constraints is within reach, allowing better RF pulse performance and faster acquisitions at ultra‐high fields at the cost of higher sequence complexity. Magn Reson Med 72:679–688, 2014. © 2013 Wiley Periodicals, Inc.